All-Inorganic p−n Heterojunction Solar Cells by Solution Combustion Synthesis Using N-type FeMnO3 Perovskite Photoactive Layer - Papadas, Ioannis T.; Ioakeimidis, Apostolos; Vamvasakis, Ioannis; Eleftheriou, Polyvios; Armatas, Gerasimos S.; Choulis, Stelios A. (Frontiers in Chemistry, 2021)
This study outlines the synthesis and physicochemical characteristics of a solution-processable iron manganite (FeMnO3) nanoparticles via a chemical combustion method using tartartic acid as a fuel and demonstrates the performance of this material as a n-type photoactive layer in all-oxide solar cells. It is shown that the solution combustion synthesis (SCS) method enables the formation of pure crystal phase FeMnO3 with controllable particle size. Moreover, to assemble a network of connected FeMnO3 nanoparticles, β-alanine was used as a capping agent and dimethylformamide (DMF) as a polar aprotic solvent for the colloidal dispersion of FeMnO3 NPs. This procedure yields a ~500 nm thick photoactive layer. The proposed method is crucial to obtain functional solution processed NiO/FeMnO3 heterojunction inorganic photovoltaics. Photovoltaic performance and solar cell device limitations of the NiO/FeMnO3-based heterojunction solar cells are presented.